Effect Of Mozart Music Therapy on Ansietas Hemodialisa Patients in DR. Achmad Mochtar Hospital Bukittinggi 2016 - Sari, Yade Kurnia (LPPM Universitas Prima Nusantara Bukittinggi, 2018)
Hemodialysis clients who were hospitalized around 43.1% experienced an anxiety condition. This is caused by Client Kidney Failure undergoing hemodialysis, requiring 12-15 hours of dialysis every week, or at least 3-4 hours per therapy. This activity will continue throughout his life. This study aims to determine the effect of Mozart's music therapy on anxiety clients who undergo hemodialysis at Achmad Mochtar Hospital Bukittinggi. The design of this study was Quasi-Experimental pre and Post-test with a total sample of 64 people, 32 people who received Mozart music therapy as many as 32 people as a control group. Using the HARS scale to determine the level of client anxiety. The results showed a significant decrease in anxiety conditions in the intervention group who received Mozart music therapy compared to those who did not receive therapy (P-value <0.05). Mozart music therapy is recommended for hemodialysis clients who experience anxiety in Achmad Mochtar Hospital Bukittinggi.